Pengaruh varietas pada berbagai konsentrasi pupuk daun terhadap pertumbuhan dan hasil tanaman stroberi (Fragaria Sp.) - Ria Megasari (Fakultas Pertanian Universitas Ichsan Gorontalo, 2019)
This research aimed to find the effect of variety on the various concentration of leaf fertilizer on growth and results of strawberries plants. This research starts from January to April 2016 in Lannying Village, Uluere District, Bantaeng Regency, South Sulawesi Province. The experiment used a Split-plot design consisted of two factors. The first factor as the main plot was a variety consisted of 3 levels, Longkoni variety, California variety, and Rosalinda variety. The second factor as a subplot was leaf fertilizer concentration (Grand-K) which consisted of 5 levels: control, 2.5 g.l–1, 5 g.l–1, 7.5 g.l–1, and 10 g.l–1 so that there were 15 treatment combinations that were repeated 3 times with a total unit experiment of 45 units. The results showed that there was an interaction between California varieties and 10 g.l–1 applied leaf fertilizer concentration on the parameters of plant height (12.04 cm) and the total of plant leaves (15.42 strands). California variety gave the best results on fruit diameter (24.58 mm) and fruit weight (8.24 g). The concentration of leaf fertilizer 10 g.l–1 water showed the best results on the parameters of fruit weight (9.56 g) and fruit diameter (26.00 mm).